Evaluating The Spatial Suitability of the Urban Expansion of Lattakia Using Spatial Analysis Methodology - Deep, Sami Sheikh; Maghrakona, Marah Ali (Latakia University Journal -Engineering Sciences Series, 2019)
Most cities are experiencing a rapid urban expansion, often spontaneously. In the city of Lattakia, urban communities spread and grew at random and accelerated without study or organization at the expense of agricultural land, these communities imposed new challenges on the concerned authorities and municipalities, the need arose to regulate and guide this growth. Therefor this research started from the question of determining the optimal future directions for the urban expansion of Lattakia until 2035 and the most suitable areas for this expansion through the use of spatial analysis methodology and modern techniques in geographic information systems that give sufficient indicators and a "complete Which gives a "complete" view of the urban environment of the city and its surroundings. The study will discuss the methodology used to study the areas of city expansion, and then assess the spatial relevance of these areas using the spatial analysis methodology, which includes the study of the factors influencing the expansion and the most suitable areas. Monitoring, study and analysis revealed that there is a lack of methodology for determining the future urban expansion areas, the future of this expansion until (2035) is the north and north-east direction, with the possibility of expansion eastward. The research stressed the need to develop the stages of study and determine the mechanisms of urban expansion and follow the analytical methodology takes into account the factors affecting it. تشهد معظم المدن توسعاً عمرانياً متسارعاً يتم في أغلب الأحيان بطريقةٍ عفوية. وقد ظهرت في محيط مدينة اللاذقية تجمعات عمرانية انتشرت ونمت بشكل عشوائي ومتسارع دون دراسة أو تنظيم على حساب الأراضي الزراعية، هذه التجمعات فرضت تحديات جديدة أمام الجهات المعنية والبلديات، فظهرت الحاجة إلى تنظيم هذا النمو وتوجيهه. لذلك انطلق هذا البحث من مسألة تحديد الاتجاهات المستقبلية المثلى للتوسع العمراني لمدينة اللاذقية حتى العام (2035) وأكثر المناطق ملاءمةً لهذا التوسع من خلال استخدام منهجية التحليل المكاني والتقنيات الحديثة في نظم المعلومات الجغرافية (GIS) التي تعطي المؤشرات الكافية وتصوراً كاملاً عن البيئة العمرانية للمدينة ومحيطها. وسيتناول البحث عرضاً للمنهجية المتبعة في دراسة مناطق توسع المدينة، ثم تقييم الملاءمة المكانية لهذه المناطق باستخدام منهجية التحليل المكاني التي تتضمن دراسة العوامل المؤثرة في التوسع وتأثير هذه العوامل مكانياً للتوصل إلى تحديد الاتجاهات المستقبلية المثلى للتوسع وأكثر المناطق ملاءمةً له. وقد تبين من خلال الرصد والدراسة والتحليل وجود قصور في المنهجية المتبعة لتحديد مناطق التوسع العمراني المستقبلي للمدينة، كما تبين أن الاتجاه المستقبلي لهذا التوسع حتى العام (2035) هو الاتجاه الشمالي والشمالي الشرقي مع وجود إمكانية للتوسع شرقاً. وأكد البحث على ضرورة تطوير مراحل دراسة وتحديد آليات التوسع العمراني واتباع منهجية تحليلية مكانية تراعي العوامل المؤثرة فيه.